RETRACTED: An Experimental Investigation on the Synthetic Ester Circulation for Drying Cellulose Insulation in Distribution Transformers - Tazhibayev, Adilbek; Amitov, Yernar; Arynov, Nurbol; Shingissov, Nursultan; Kural, Askat (Engineering, Technology & Applied Science Research, 2024)
This article has been been retracted at the request of the Editor-in-Chief due to extended similarites with a previously published article. The previously published article is: P. Przybylek, K. Walczak, W. Sikorski, H. Moscicka-Grzesiak, H. Moranda and M. Cybulski, "Experimental Validation of a Method of Drying Cellulose Insulation in Distribution Transformers Using Circulating Synthetic Ester," in IEEE Access, vol. 9, pp. 150322-150329, 2021, doi: 10.1109/ACCESS.2021.3125840